2023
DOI: 10.1177/02692155231162423
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular dysfunction in people who fall: A systematic review and meta-analysis of prevalence and associated factors

Abstract: Objectives To evaluate the prevalence and factors associated with vestibular dysfunction in people who fall. Data Sources All electronic records from MEDLINE, CINAHL, Embase and psycINFO databases were searched to 9 December 2022. Review Methods Participants were adults with at least one fall within the previous year who were exposed to at least one vestibular function test. Any published peer reviewed trial designs were accepted. Included studies were assessed for risk of bias using a modified Epidemiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The physiological degeneration of the vestibular system can be easily ignored by older individuals due to its slow progression. However, damage to the body's balance ability accumulates over time, resulting in exercise intolerance, instability, and gait issues [24]. This study also found that the ability of older patients in the OH group to control their direction decreased.…”
Section: Discussionmentioning
confidence: 53%
“…The physiological degeneration of the vestibular system can be easily ignored by older individuals due to its slow progression. However, damage to the body's balance ability accumulates over time, resulting in exercise intolerance, instability, and gait issues [24]. This study also found that the ability of older patients in the OH group to control their direction decreased.…”
Section: Discussionmentioning
confidence: 53%
“…Adults over 40 with vestibular dysfunction have a 12-fold increase in the odds of falling ( 25 ). BPPV has been correlated to falls ( 4 , 6 , 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Transient subjective dizziness or vertigo with nystagmus in the plane of the involved semicircular canals from positional testing are diagnostic of definite BPPV (2). If left untreated, BPPV is correlated with a decrease in activities of daily living scores, an increased rate of falling, and increased rates of depression (3)(4)(5)(6). According to the American Academy of Otolaryngology-Head and Neck Surgery (AAHN) 2018 Clinical Practice Guidelines and recommendations by the American Academy of Neurology, positional tests are the gold standard for diagnosing BPPV, with strong recommendations for treating BPPV with canalith repositioning maneuvers (3,7).…”
Section: Introductionmentioning
confidence: 99%
“…Most patients with VS have vestibular deficits in the tumor-affected ear [7], and numerous studies have presented the risk of fall-related injury among patients with asymmetric vestibular function originating from other vestibular disorders [33][34][35][36]. According to Donovan et al, more than one in two patients who suffered falls had objective signs of vestibular deficit [37]. Baldursdottir et al reported an increased prevalence of vestibular deficits in patients aged 50-75 years with fall-related wrist fractures [38].…”
Section: Plos Onementioning
confidence: 99%